Computing (mod iLs(X)/F (Tm)+2iLs(X)/F
(X)
KmF (X)), by Lemma 2.2 (ii) we find
σLs
s
i=1
(
2{

pri (y + ri)/x(℘(ri) + b), mi(
i
+

pri )} χi
)
=
s
i=1
(
2{

pri (y + ri), mi(
i
+

pri )} χi
)
+
s
i=1
(
2{a/(℘(ri) + b), mi(
i
+

pri )} χi
)
2{ax}
s
i=1
(
{mi(
i
+

pri )} χi
)
=
s
i=1
2
(
{

pri ,
i
+

pri } χi + {

pri , mi} χi
)
+
s
i=1
(
{(y + ri), mi
2( 2
i
+ pri )} χi
)
+
s
i=1
(
{a/(℘(ri) + b), mi
2( 2
i
+ pri )} χi
)
{ax}
s
i=1
(
{mi
2( 2
i
+ pri )} χi
)
However, we can express
2{

pri ,
i
+

pri } = 2{

pri
i
+

pri
,
i
} = {
pri
2
i
+ pri
,
i
} K2Ls
and so as pri aNL/F L and as {
i
, mi
2}
χi 2KmF
s
i=1
2
(
{

pri ,
i
+

pri } χi + {

pri , mi} χi
)
=
s
i=1
{
pri
2
i
+ pri
,
i
} χi + {pri , mi} χi

s
i=1
(
{ i,
2
i
+ pri } χi + { i, mi
2}
χi
)
=
s
i=1
(
{ i, mi
2( 2
i
+ pri )} χi
)
(mod (iLs(X)/F (Tm) + 2iLs(X)/F
(X)
KmF (X))).
Now,
∑s
i=1
(
{mi 2( 2
i
+ pri )} χi
)
= 2χ∞ 2KmF by Lemma 1.4 and and as
a, ℘(ri) + b, pri NL/F L aNL/F L we can extract the remaining terms from the
Previous Page Next Page